Book Review - Dyd Samarawickrama (Paediatric Dentistry, 2004)
This book is a major new work on a subject of vital concern to all dentists. It builds on the work of two former books, Textbook of Clinical Cariology, and Fluoride in Dentistry, to present a definitive resource on caries prevention and treatment.